The immature stages of Phylloicus lituratus (Trichoptera: Calamoceratidae) with new records of Phylloicus and Banyallarga species in northwestern Argentina and southern Bolivia - Martín, Paola A. Rueda (Zootaxa, 2013)
Phylloicus lituratus Banks 1920 larva and pupa were associated. It is a new record for Argentina and represents the most austral record for the species. New records of other Calamoceratidae species are provided also from northwestern Argen-tina and southern Bolivia. Banyallarga (B.) argentinica Flint 1983 is recorded for the first time for Bolivia; B. (B.) loxana (Navás 1934) and B .(B.) yungensis Flint 1983 are both newly recorded from Salta province in northwestern Argentina. Illustrations of male genitalia of all species and of immature stages of P. lituratus are included. Presence of a Banyallarga larva in a leaf case suggests a need to change some larval keys used to identify the two endemic genera of Neotropical Calamoceratidae.